Documenting State Violence: (Symbolic) Annihilation & Archives of Survival - Solis, Gabriel (KULA)

(untitled) (University of Victoria Libraries, 2018)
This essay explores symbolic annihilation in the context of state violence, including policing, incarceration, and the death penalty in the US. Using auto-ethnography to reflect on the work of the Texas After Violence Project (TAVP) and other community-based documentation and archival projects, I argue that the personal stories and experiences of victims and survivors of state violence are critical counter-narratives to dominant discourses on violence, criminality, and the purported efficacy of retributive law enforcement and criminal justice policies and practices. They also compel us to engage with complex questions about victimhood, disposability, and accountability. Building on the work of activists and archivists engaged in liberatory memory work, I also argue that counter-narratives of state violence confront and challenge the social, cultural, and ideological power of symbolic annihilation. Because these counter-narratives are under constant threat of being suppressed, co-opted, or silenced, they are forms of endangered knowledge that must be protected and preserved. Finally, I reflect on ‘archives of survival,’ repositories of stories and other ephemera of tragedy that contribute to envisioning and achieving transformative justice.